Comparison of maxillary sinus on radiograph among males and females - Rona Aulianisa; Rini Widyaningrum; Isti Rahayu Suryani; Rurie Ratna Shantiningsih; Munakhir Mudjosemedi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: An obstacle in forensic odontology is an incomplete body caused by post-mortem damage. The problem can be solved by using lateral cephalometric radiographs for victim identification. Sex determination can be performed on the maxillary sinus, which is the largest among the paranasal sinuses. Purpose: This study aims to analyse the maxillary sinuses’ width and height on lateral cephalometric radiographs among male and female subjects. Methods: The study samples were 60 lateral cephalometric radiographs (30 males and 30 females) between the ages of 20 and 40, with complete permanent dentition (or third molar absence). The height and the width of maxillary sinus measurement were performed using measurement tools of EzDent-i Vatech Software. Results: The average width of the maxillary sinus on males was 40.60 ± 1.56 mm, and the height was 35.02 ± 2.09 mm, while the width and the height on females were 36.93 ± 1.30 mm and 29.72 ± 1.76 mm, respectively. The independent t-test reveals a significant difference (p<0.05) between males and females, both in the maxillary sinus’s width and height on the lateral cephalometric radiograph. Conclusion: The maxillary sinus in males is larger than in females, it opening up possibilities for disaster victim identification.